(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The field of English Language Teaching (ELT) is undergoing rapid transformation due to technological advancements, globalization, and changing learner needs. This paper explores innovative pedagogical approaches that are reshaping classroom practices in ELT. It examines the theoretical underpinnings of communicative, learner-centered, and technology-integrated methods, and analyzes their implementation through practical examples. The findings show that when theory is effectively translated into classroom practice, student engagement, motivation, and proficiency levels significantly improve.